Prolyl Endopeptidase Gene Disruption Improves Gut Dysbiosis and Non-alcoholic Fatty Liver Disease in Mice Induced by a High-Fat Diet - Jiang, Daixi; Zhang, Jianbin; Lin, Shuangzhe; Wang, Yuqin; Chen, Yuanwen; Fan, Jiangao (Frontiers in Cell and Developmental Biology, 2021)
The gut-liver axis is increasingly recognized as being involved in the pathogenesis and progression of non-alcoholic fatty liver disease (NAFLD). Prolyl endopeptidase (PREP) plays a role in gut metabolic homeostasis and neurodegenerative diseases. We investigated the role of PREP disruption in the crosstalk between gut flora and hepatic steatosis or inflammation in mice with NAFLD. Wild-type mice (WT) and PREP gene knocked mice (PREPgt) were fed a low-fat diet (LFD) or high-fat diet (HFD) for 16 or 24 weeks. Murine gut microbiota profiles were generated at 16 or 24 weeks. Liver lipogenesis-associated molecules and their upstream mediators, AMP-activated protein kinase (AMPK) and sirtuin1 (SIRT1), were detected using RT-PCR or western blot in all mice. Inflammatory triggers and mediators from the gut or infiltrated inflammatory cells and signal mediators, such as p-ERK and p-p65, were determined. We found that PREP disruption modulated microbiota composition and altered the abundance of several beneficial bacteria such as the butyrate-producing bacteria in mice fed a HFD for 16 or 24 weeks. The level of butyrate in HFD-PREPgt mice significantly increased compared with that of the HFD-WT mice at 16 weeks. Interestingly, PREP disruption inhibited p-ERK and p-p65 and reduced the levels of proinflammatory cytokines in response to endotoxin and proline-glycine-proline, which guided macrophage/neutrophil infiltration in mice fed a HFD for 24 weeks. However, at 16 weeks, PREP disruption, other than regulating hepatic inflammation, displayed improved liver lipogenesis and AMPK/SIRT1 signaling. PREP disruption may target multiple hepatic mechanisms related to the liver, gut, and microbiota, displaying a dynamic role in hepatic steatosis and inflammation during NAFLD. PREP might serve as a therapeutic target for NAFLD.